Joint Commitment, Human Life and Social Ontology - Francesca De Vecchi (Rosenberg & Sellier, 2016)
In this introductory chapter, we recall some of the crucial aspects of Gilbert’s notion of joint commitment. Special attention is devoted to the importance of this notion both for human life in its social aspects (notably, the formation of group beliefs and the constituions of just joint commitments) and for social ontology (in particular, for the understanding of norm and institutions and of the intentionality of groups). Then, we briefly summarize the contents of the contributions collected in the issue.